2010
DOI: 10.1002/art.27428
|View full text |Cite
|
Sign up to set email alerts
|

Inducible costimulator ligand regulates bleomycin‐induced lung and skin fibrosis in a mouse model independently of the inducible costimulator/inducible costimulator ligand pathway

Abstract: Objective. Systemic sclerosis is a connective tissue disease characterized by fibrosis of the skin and internal organs, including the lungs. Inducible costimulator (ICOS), which is expressed on activated T cells, and its ligand ICOSL, which is expressed on antigen-presenting cells, have been considered a single receptor-ligand pair. Although the ICOS/ICOSL pathway is known to play various roles in adaptive immunity, its roles in innate immunity and tissue fibrosis remain unknown.Methods. We assessed the roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…Several recent studies, including our bleomycin model, showed the roles of ICOS and ICOSL in innate immune responses, including inflammation. 22,23 Our findings also suggest that ICOS-ICOSL signaling contributes to innate immunity during wound healing. Alternatively, ICOS-ICOSL signaling may affect cytokine balance or the production of cytokines in organs such as the skin under homeostatic and pathological conditions.…”
Section: 32supporting
confidence: 55%
See 1 more Smart Citation
“…Several recent studies, including our bleomycin model, showed the roles of ICOS and ICOSL in innate immune responses, including inflammation. 22,23 Our findings also suggest that ICOS-ICOSL signaling contributes to innate immunity during wound healing. Alternatively, ICOS-ICOSL signaling may affect cytokine balance or the production of cytokines in organs such as the skin under homeostatic and pathological conditions.…”
Section: 32supporting
confidence: 55%
“…In fact, recent studies suggest involvement of ICOS and ICOSL in innate immune disease models. 22,23 As skin wound healing involves a strong innate immune component, we applied this model to mice deficient for ICOS and ICOSL to investigate the roles of these molecules in modulating innate immunity.…”
Section: Skin Wound Healing Is Mediated By Inflammatory Cell Infiltramentioning
confidence: 99%
“…Bleomycin (Nippon Kayaku) was dissolved in PBS at a concentration of 1 mg/ml and sterilized by filtration as described previously (33,34). Bleomycin (100 ml) was injected intradermally into the shaved back of the 8 wk-old male BALB/cAJcl mice daily for 4 wk.…”
Section: Bleomycin-induced Skin Fibrosis In Micementioning
confidence: 99%
“…Bleomycin (300 mg) or PBS was injected intradermally into the shaved back of 6-wk-old C57BL/6 mice daily for 4 wk, as described previously (39,40). The back skin was removed on the next day after the final injection, fixed in 10% formalin solution, and embedded in paraffin.…”
Section: Intradermal Treatment With Bleomycinmentioning
confidence: 99%